Scalable magnet geometries enhance tumour targeting of magnetic nano-carriers. (June 2020) - Mohseni, Matin; Connell, John J.; Payne, Christopher; Patrick, P. Stephen; Baker, Rebecca; Yu, Yichao; Siow, Bernard; Zaw-Thin, May; Kalber, Tammy L.; Pankhurst, Quentin A.; Lythgoe, Mark F.
Abstract: Targeted drug delivery systems aim to increase therapeutic effect within the target tissue or organ, while reducing off-target toxicity associated with systemic delivery. Magnetic drug targeting has been shown to be an effective strategy by manipulating therapeutics inside the body using a magnetic field and an iron oxide carrier. However, the effective targeting range of current magnets limits this method to small animal experiments or superficial parts of the human body. Here we produce clinically translatable magnet designs capable of increasing exposure of tissue to magnetic fields and field gradients, leading to increased carrier accumulation. The iron oxide nanoparticle capturing efficiency was first assessed in vitro using a simple vascular flow system. Secondly, accumulation of these particles, following magnetic targeting, was evaluated in vivo using a range of different magnet designs. We observed that our bespoke magnet produced a 4-fold increase in effective targeting depth when compared to a conventional 1 T disk magnet. Finally, we show that this magnet is readily scalable to human size proportions and has the potential to target 100 nm particles up to a depth of 7 cm at specific locations of human body. Graphical abstract: Unlabelled Image Highlights: Magnetic tumour targeting of 100 nm iron-oxide nanoparticles was investigated using a range of different magnet designs. The bespoke encompassing magnet increased the effective targeting depth when compared to a conventional disk magnet. This magnetic setup can be up-scaled to target 100 nm particles up to a depth of 7cm within human body.